Friction fade-out at polymer-like carbon films slid by ZrO2 pins under hydrogen environment. (August 2015) - Nosaka, Masataka; Mifune, Akira; Kawaguchi, Masahiro; Shiiba, Takashi; Kato, Takahisa
Friction tests using ceramic pins against fully hydrogenated diamond-like carbon (polymer-like carbon, PLC) film under H2 /He mixed gas or pure H2 gas environment were conducted. The test results of ZrO2 (YSZ: yttria-stabilized zirconia) pin slid against PLC film with an applied load of 4.9 N showed that the friction coefficient dropped to the tribometer noise level (friction fade-out, FFO) as low as 0.0002. In another experiment with the same materials and with an applied load of 30.4 N, the friction coefficient dropped to 0.0001–0.0005, which continued more than 4 h. Optical microscope and scanning electron microscopic observations, nano-indentation, surface profiler, X-ray photoelectron spectroscopy, Raman, and time-of-flight secondary ion mass spectrometry measurements were conducted and the mechanism for inviting FFO is investigated. It is found by an optical microscopic observation that the transfer film has small blisters, indicating some gaseous substance is generated at the ZrO2 surface. It is discussed based on the measurements that ZrO2 catalysis plays very important roles for gaseous substances generation and for H-passivation on both PLC and transfer film surfaces, which are closely relating to FFO through gas-lubrication effect, and through reducing adhesive force, respectively.